2008
DOI: 10.1074/jbc.m802320200
|View full text |Cite
|
Sign up to set email alerts
|

Ajuba Functions as a Histone Deacetylase-dependent Co-repressor for Autoregulation of the Growth Factor-independent-1 Transcription Factor

Abstract: Growth factor independent-1 (Gfi1) is a zinc finger protein with a SNAG-transcriptional repressor domain. Ajuba is a LIM domain protein that shuttles between the cytoplasm and the nucleus. Ajuba functions as a co-repressor for synthetic Gfi1 SNAG-repressor domain-containing constructs, but a role for Ajuba co-repression of the cognate DNA bound Gfi1 protein has not been defined. Co-immunoprecipitation of synthetic and endogenous proteins and co-elution with gel filtration suggest that an endogenous Ajuba⅐Gfi1⅐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 42 publications
(24 reference statements)
1
40
0
Order By: Relevance
“…Ajuba further recruits Prmt5 and HDACs through its preLIM region to repress E-cadherin expression, a known Snail target gene. 17,18,20,21 Moreover, we demonstrated that Ajuba contains functional NR boxes and directly interacts with RARα, 22 where Ajuba functions as a co-repressor and negatively regulates RAR signaling. Here, we describe the novel findings that Ajuba interacts with PPARγ via its non-NR box module within the preLIM region and functions as a co-activator for PPARγ by recruiting p300/CBP via its LIM domain.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Ajuba further recruits Prmt5 and HDACs through its preLIM region to repress E-cadherin expression, a known Snail target gene. 17,18,20,21 Moreover, we demonstrated that Ajuba contains functional NR boxes and directly interacts with RARα, 22 where Ajuba functions as a co-repressor and negatively regulates RAR signaling. Here, we describe the novel findings that Ajuba interacts with PPARγ via its non-NR box module within the preLIM region and functions as a co-activator for PPARγ by recruiting p300/CBP via its LIM domain.…”
mentioning
confidence: 79%
“…In the nucleus, Ajuba functions as a co-repressor for various transcription factors such as Gfi-1, Snail and ISI1 by recruiting HDACs and PRMT5. 17,18,20,21,41 We recently discovered that Ajuba contains three conserved functional nuclear receptor (NR) boxes mediating a direct interaction with RARα and functions as a typical co-repressor for RARα in a ligand-dependent manner. 22 Here, we demonstrate that Ajuba interacts with PPARγ by different mechanism: the conserved NR boxes of Ajuba do not contribute to the interaction between Ajuba and PPARγ, instead, a region in the preLIM is required for the interaction with PPARγ; Ajuba binds the DNA-binding domain of PPARγ in a ligand-independent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gfi1 can bind consensus DNA target sequences by a C-terminal zinc-finger domain and repress transcription by its N-terminal SNAG domain, 15 in part by recruiting corepressors. [16][17][18][19] Besides acting as a transcriptional repressor, Gfi1 interacts with protein inhibitor of activated signal transducer and activator of transcription (STAT), which can bind to and inhibit STAT3 signaling. 20 As a result, Gfi1 can relieve STAT3 from protein inhibitor of activated STAT3-induced inhibition, resulting in enhanced STAT3 signaling.…”
Section: Introductionmentioning
confidence: 99%